Standard handbook of stamp collecting - Cabeen, Richard McP, 1887 - 1969 (Thomas Y. Crowell Publishers, 1979)
A guide to stamp collecting, with information on every aspect of beginning and developing a collection, identifying stamps, and technical matters, plus a table of the world's stamps and a guide to inscriptions in other alphabets.